Pengaruh Etika Audit dan Motivasi Terhadap Keputusan Strategis Internal Auditor - Mariana, Mariana; Laisa Liza; Sri Winarsih Ramadana; Rahmaniar, Rahmaniar; Zulfikar, Zulfikar (Politeknik Ganesha Medan, 2024)
This research investigates the impact of audit ethics and motivation on the strategic decisions made by internal auditors. Utilizing a multiple linear regression analysis, the study focuses on a population comprising auditors from 23 Regency/City Inspectorates in Aceh Province, with a sample size of 64 individuals. The findings reveal a significant positive influence of both audit ethics and motivation on internal auditors' strategic decisions. This suggests that heightened levels of audit ethics and motivation are associated with more favorable strategic decision-making by internal auditors. The implications of these results highlight the importance of fostering an ethical culture and motivation within the audit profession. However, it is crucial to acknowledge the limitations of the study, and further research is recommended to explore additional variables and enhance the generalizability of the findings.